Slow Wave Sleep and REM Sleep Awakenings Do Not Affect Sleep Dependent Memory Consolidation - Genzel, Lisa (Associated Professional Sleep Societies, LLC, 2009)
STUDY OBJECTIVES: The effects of REM sleep and slow wave sleep (SWS) deprivation on sleep-dependent motor and declarative memory consolidation. DESIGN: Randomized, within-subject, cross-over study SETTING: Weekly (women: monthly) sleep laboratory visits, with retest 60 hours later PARTICIPANTS: Twelve healthy subjects (6 men) aged between 20 and 30 years INTERVENTIONS: REM sleep deprivation, SWS deprivation, or undisturbed sleep MEASUREMENTS AND RESULTS: We deprived subjects once each of REM sleep and SWS, and once let them sleep undisturbed through the night. After each night, we tested declarative and procedural memory consolidation. We tested memory performance by a verbal paired associate task and a sequential finger-tapping task at 21:00 on the study night and again 60 hours later. Although REM sleep and SWS awakenings led to a significant reduction of the respective sleep stages, memory consolidation remained unaffected. We also found a significant correlation between the declarative task and sleep spindles in the undisturbed condition, especially the sleep spindles in the first third of the night. CONCLUSION: We suggest that word-pair learning relies on stage 2 sleep spindles and requires little SWS. Their sleep dependent consolidation is not affected by SWS deprivation. Simple motor tasks may either be consolidated in stage 2 sleep or depend on only small amounts of REM sleep. Their sleep dependent consolidation is not influenced by REM sleep deprivation. CITATION: Genzel L; Dresler M; Wehrle R; Grözinger M; Steiger A. Slow wave sleep and REM sleep awakenings do not affect sleep dependent memory consolidation. SLEEP 2009;32(3):302–310.